Multimeric RGD-Based Strategies for Selective Drug Delivery to Tumor Tissues - Jordan Cossu; Fabien Thoreau; Didier Boturyn (MDPI AG, 2023)
RGD peptides have received a lot of attention over the two last decades, in particular to improve tumor therapy through the targeting of the αVβ3 integrin receptor. This review focuses on the molecular design of multimeric RGD compounds, as well as the design of suitable linkers for drug delivery. Many examples of RGD-drug conjugates have been developed, and we show the importance of RGD constructs to enhance binding affinity to tumor cells, as well as their drug uptake. Further, we also highlight the use of RGD peptides as theranostic systems, promising tools offering dual modality, such as tumor diagnosis and therapy. In conclusion, we address the challenging issues, as well as ongoing and future development, in comparison with large molecules, such as monoclonal antibodies.